A cross sectional study on factors influencing attendance to eye screening - Mat Isa, Rif’atunnailah; Saidi, Sanisah; Salam, Adzura; Jamaludin, Thandar Soe Sumaiyah (2019)
Introduction: Diabetes Mellitus (DM) is on a rising trend globally and the complications of DM particularly diabetic retinopathy are kept on escalating. However, the number of patients who underwent proper eye screening in Malaysia is still unsatisfactory. Methods: This cross-sectional survey was carried out among 170 DM patients using self-administered questionnaires. The data was analyzed by using SPSS in understanding the facilitators and barriers for eye screening among DM patients. Chi-square test was used for the relationship between sociodemographic data, the knowledge score, and the frequency of eye screening. Results: Majority of participants 45.9 % (n=78) highlighted that lack of information regarding diabetes and not understanding the significance of eye screening are the barriers to eye screening. Whereas, 10.6% (n=18) reported lack of access to healthcare facilities, 6.5% (n=11) experienced time limitation and 2.9% (n=5) suffered financial issues. However, more than half of participants (58.2%) have good knowledge related to diabetic eye complication. There was a significant difference between educational level with patients’ attendance in yearly eye screening; χ2 = 8.32, df = 2, p<0.05. Conclusion: Lack of information received by the patients on the importance of eye screening and communication issues seems to be prominent and become the reasons for patients not attending eye screening. For further research, the improvement of default tracking systems and the provision of eye-related educational material are important to enhance health literacy among diabetic patients and the population of Malaysia.